2016
DOI: 10.1093/femsec/fiw178
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic factors ofPeltigeralichens influence the structure of the associated soil bacterial microbiota

Abstract: Definition of lichens has evolved from bi(tri)partite associations to multi-species symbioses, where bacteria would play essential roles. Besides, although soil bacterial communities are known to be affected by edaphic factors, when lichens grow upon them these could become less preponderant. We hypothesized that the structure of both the lichen microbiota and the microbiota in the soil underneath lichens is shaped by lichen intrinsic and extrinsic factors. In this work, intrinsic factors corresponded to mycob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 58 publications
3
28
0
Order By: Relevance
“…Previously, 50 lichen samples from two forested sites in the Coyhaique National Reserve in southern Chile, were identified by phylogenetically related sequences of cyanobacterial small sub-unit (SSU) rDNA and fungal large sub-unit (LSU) rDNA with sequences previously reported for Nostoc and Peltigera . This way, we defined five cyanobiont (C01, C03, C10, C12, and C14) and six mycobiont (M1, M2, M4, M5, M6, and M8) haplotypes [ 42 ]. In our previous phylogenetic analysis [ 24 ], most of our mycobionts formed defined and well-supported monophyletic groups with some of the Peltigera species downloaded from the database: M1 was closely-related to P. ponojensis , M2 to P. extenuata , M4 to P. rufescens , and M6 to P. frigida .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, 50 lichen samples from two forested sites in the Coyhaique National Reserve in southern Chile, were identified by phylogenetically related sequences of cyanobacterial small sub-unit (SSU) rDNA and fungal large sub-unit (LSU) rDNA with sequences previously reported for Nostoc and Peltigera . This way, we defined five cyanobiont (C01, C03, C10, C12, and C14) and six mycobiont (M1, M2, M4, M5, M6, and M8) haplotypes [ 42 ]. In our previous phylogenetic analysis [ 24 ], most of our mycobionts formed defined and well-supported monophyletic groups with some of the Peltigera species downloaded from the database: M1 was closely-related to P. ponojensis , M2 to P. extenuata , M4 to P. rufescens , and M6 to P. frigida .…”
Section: Resultsmentioning
confidence: 99%
“…To carry out the metabolic profiling, composite samples from the lichen thallus and the associated substrate were prepared, grouping them by site (S1 and S2), mycobiont type (M), and cyanobiont type (C). This arrangement produced 11 samples from lichen thalli and 11 samples from the underlying substrates [ 42 ]. The kinetics of the consumption of carbon-sources of all samples were adjusted to the modified Gompertz equation, determining that at 48 h all the communities were in the exponential phase of color development ( Appendix A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences are thought to be driven by biotic and abiotic factors, of which the photobiont and large-scale geographical distance apparently determine the composition in different lichen types (29). It has also been suggested that a lichen's secondary metabolite production could drive microbiome structure (29,55,56). In this work, we used a differential abundance analysis approach (ALDEx2) to identify OTUs that varied in abundance among samples.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing our results with those of other studies [10][11][12][13][14][15][16] using our protocol, we managed to obtain more stable growth curves for AWCD, particularly in the constant phase and relatively low values of SD (Figure 2A). Another important remark is that the inoculum could be relativized simply resuspending soil mass, in order to not to artificially homogenize differences that are intended to be detected among the different soil samples of the same experiment [17][18][19][20]. In order to avoid this possible artefact, in our case, the same dilution (leading to~10 4 CFUs mL −1 ) was chosen for all the samples analysed in the same experiment.…”
Section: Influence Of Bacterial Inoculum Densitiesmentioning
confidence: 99%